O altar como palco um estudo de caso sobre a Church City - Santos, Márcia Maria dos (2023)
This dissertation aimed to investigate the movements and changes of Protestantism, especially the Presbyterian segment in the current Brazilian religious context of the twenty-first century from the church-spectacle-communication relationship. For this, we focus our gaze on Church City/Anápolis-GO, more specifically, the space where the pulpit rests (object of our study). The motivation for the choice of religious unity is justified because of its novelty and differential in the transmission of religious content that has the space of the pulpit as centrality and metaphor of the current way of communicating religion. Therefore, due to the involvement of the pandemic by the SARS-CoV-2 virus (covid 19/coronavirus) and its developments, we had as an essential source for the study the views transmitted by YouTube (live and recordings) in the period that comprised 2020 to 2022. Thus, for the elaboration of this dissertation, we anchored ourselves in the questions that would reveal what would be the characteristic of the pulpit space, how would be its relationship with the people who attend the church and finally, as an unfolding, if we would be in front of a stage or an altar. an altar. In this sense, we defend that the technology materialized by the media resources (internet, big screens, lighting resources) common to the shows and present throughout the services, contributes to the strengthening of the church-faithful relationship, especially of young people, in the communication of religious content. Church City, finally, is configured as a disruptive church with reinvigorated and attractive religious language whose stage/altar, which we sometimes call, is configured in synthesis with a space and support of supporting relevance for the transmission of the religious message. Exemplary of these times, it is proof that the church has not lost strength or importance, but that it has found other ways to communicate with the religious